Hayek and the Nobel Prize - Rothbard, Murray N. (2014)
In this text, for the occasion of the Nobel Prize in economics awarded to Hayek, the author summarizes the main contributions of this author to economic theory, methodology and political philosophy, noting the importance of his ideas to the resistance to inflationism, central planning and macroeconomic activism. They characterized the twentieth century.